The Integration of Metagenomics and Chemical Physical Techniques Biodecoded the Buried Traces of the Biodeteriogens of Parchment Purple Spots - Perini, Nicoletta; Mercuri, Fulvio; Orlanducci, Silvia; Thaller, Maria Cristina; Migliore, Luciana (Frontiers in Microbiology, 2020)
Ancient parchments record an immense part of our cultural heritage, having been used as the main written support material for centuries. Parchment easily undergoes biodeterioration, whose main signs are the so-called purple spots, which often lead to detachment of the superficial written layer. Up to recent years, several studies have been analysing damaged parchments from different world’s archives, trying to trace back the culprit of the purple spots. However, standard cultivation and early molecular techniques have been demonstrated to be unsuccessful, leading the parchment damage issue remaining unsolved for many years. Nowadays, some studies have explored the parchment biodeterioration dynamics by adopting a multidisciplinary approach combining standard microbiological methods with high‐throughput molecular, chemical and physical techniques. This approach allowed an unprecedented level of knowledge on the complex dynamics of parchment biodeterioration. This minireview discusses the application of the combination of basic and high-throughput techniques to study historical parchments, highlighting the strengths and weaknesses of this approach. In particular, it focuses on how metagenomics has been paramount for the unequivocal identification of the microbial main actors of parchment biodeterioration and their dynamics, but also on how metagenomics may suffer the distortion inflict by the historical perspective on the analysis of ancient specimens. As a whole, this minireview aims to describe the scenario of information on parchment biodeterioration obtained so far by using the integration of metagenomic with recent chemical (Raman spectroscopy) and physical (Light Transmission Analysis) approaches, which might have key implications in the preservation of many ancient documents.